2000
DOI: 10.1097/00005537-200002010-00020
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sinus Surgery Using Intraoperative Computed Tomography Imaging for Updating a Three‐Dimensional Navigation System

Abstract: Objectives: The use of three-dimensional navigation systems provides information on the structures surrounding the field of operation and thereby reduces the risk of iatrogenic damage. The computed tomography (CT) data conventionally used are provided by preoperative scanning procedures, which means that tissue changes coming about during surgery are not seen on the screen. An intraoperative CT scanning procedure being able to update the CT data could provide a solution. Study Design: Endoscopic s inus operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 15 publications
2
31
0
1
Order By: Relevance
“…This means that addition of landmarks to surface registration did not improve accuracy of surgical navigation. Overall, the TRE values observed in this study were within the range reported in other studies of electromagnetic registration [13,15,[21][22][23][24]. We were also interested, how accuracy of surface registration compares to the reference registration mode using bone anchored fiducials applied before the preoperative CT scan.…”
Section: Addition Of Landmark Registration To Surface Registration DIsupporting
confidence: 80%
“…This means that addition of landmarks to surface registration did not improve accuracy of surgical navigation. Overall, the TRE values observed in this study were within the range reported in other studies of electromagnetic registration [13,15,[21][22][23][24]. We were also interested, how accuracy of surface registration compares to the reference registration mode using bone anchored fiducials applied before the preoperative CT scan.…”
Section: Addition Of Landmark Registration To Surface Registration DIsupporting
confidence: 80%
“…Cartellieri et al stated that the system provides the surgeon with higher precision of the threedimensional navigation systems, recognition of intraoperative tissue changes, and an improved feeling of assurance. 5 On the other hand, the patients are repeatedly exposed to radiation and prolonged anesthesia. In addition, both technical and personnel resources are higher with the associated added cost burden.…”
Section: Discussionmentioning
confidence: 99%
“…The high accuracy and reliability of this novel registration device was proven by the measurement of values in the submillimetric range for target fiducials located in the lateral skull base region, which almost matched the accuracy of fixed bone-implanted marker registration. Although the more distant targets yielded slightly larger values, confirming the significant impact of the distance between the registration and target points on the accuracy [7,8,21], even the maximum deviation of 1.2 mm is still within the range (1 to 2 mm) that is often considered ''clinically acceptable'' for navigation system accuracy [1,21,25,26]. Maxillary splint-based systems with extraoral extensions for reference markers have been used previously with sufficient navigational accuracy in neurosurgery (0.29-0.86 mm [17], 0.0-2.0 mm [27]), in sinus surgery (1.56 AE 0.76 mm [28]), and in the temporal region (0.73 AE 0.25 mm [17,29]); however, only a few of these systems have been tested for targets in the lateral skull base region [15,29,30,31].…”
Section: Discussionmentioning
confidence: 57%
“…They are widely accepted as useful tools for intraoperatively identifying important anatomical structures and assisting in the exact positioning of surgical instruments, especially when conditions are complex because of the loss of surgical landmarks as a result of previous surgeries or tumor destruction [1][2][3].…”
Section: Introductionmentioning
confidence: 99%